Twenty-Five Years Travelling the Publication Road: The Profile Journal Life Story - Melba Libia Cárdenas (Profile: Issues in Teachers' Professional Development)
This article presents the life story of Profile. The story is based on an ethnographic case study that aimed to understand the viewpoints of Profile’s new writers and reviewers regarding the role of scientific journals in fostering communities in the knowledge society. To gather information, I relied on personal reflections from my experience as the creator and editor of the journal, along with documentary evidence (published issues, regularly collected statistics, editorial workflows, and communications with editorial teams and various bodies of Universidad Nacional de Colombia, which funds the publication). The story illustrates the inception, development, and primary challenges that need to be addressed to ensure its continuity.